2022
DOI: 10.1002/spp2.1453
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal taphonomy of anurans from the Eocene Geiseltal Konservat‐Lagerstätte, Germany: insights into the controls on fossil anuran preservation

Abstract: The Geiseltal biota is an Eocene lacustrine Konservat-Lagerst€ atte in central Germany. Despite its rich fauna and flora (over 50 000 fossil vertebrates, insects and other invertebrates, plants and trace fossils) the taphonomy of the biota, and of the anurans in particular, is poorly understood. We analysed the skeletal taphonomy of 168 anurans, scoring each specimen for orientation, completeness and articulation. Most are partial skeletons, truncated during preparation. This process introduces measurable arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 111 publications
(170 reference statements)
0
17
0
Order By: Relevance
“…Martinez‐Delclòs & Martinell 1993; Falk et al . 2022). In addition, some elements of the former biocoenosis could have escaped preservation, while biotas from surrounding terrestrial and aquatic environments entered the limnic setting (see Briggs et al .…”
Section: Discussionmentioning
confidence: 99%
“…Martinez‐Delclòs & Martinell 1993; Falk et al . 2022). In addition, some elements of the former biocoenosis could have escaped preservation, while biotas from surrounding terrestrial and aquatic environments entered the limnic setting (see Briggs et al .…”
Section: Discussionmentioning
confidence: 99%
“…The most likely cause of death for the female represented by JQ-HX-QW-02 is drowning or exhaustion in relation to mating, constituting the first Mesozoic case of death linked to mating behaviour (figure 6). This latter cause of death has also been considered to be a major cause of death in some Cenozoic anurans [79,8185].
Figure 6Reconstructed Early Cretaceous living environment of the Gansubatrachus qilianensis .
…”
Section: Discussionmentioning
confidence: 99%
“…Instead, refloating may have been prevented by low temperatures and/or deep waters. At low temperatures, low rates of decay and thus of gas production (plus ongoing escape of gases via various orifices) can inhibit the accumulation of sufficient gases for carcasses to become buoyant 79 , 80 ; experimental work has demonstrated that, below about 16 °C, fish carcasses can remain on the water bottom for weeks to months without floating 80 . In deep waters, high hydrostatic pressure compresses decay gases and results in their dissolution, thereby suppressing flotation of the carcasses 79 , 80 .…”
Section: Discussionmentioning
confidence: 99%
“…At low temperatures, low rates of decay and thus of gas production (plus ongoing escape of gases via various orifices) can inhibit the accumulation of sufficient gases for carcasses to become buoyant 79 , 80 ; experimental work has demonstrated that, below about 16 °C, fish carcasses can remain on the water bottom for weeks to months without floating 80 . In deep waters, high hydrostatic pressure compresses decay gases and results in their dissolution, thereby suppressing flotation of the carcasses 79 , 80 . Consistent with this cold, deep water scenario, previous palaeoclimatic reconstruction for the Jehol Biota indicates cold local conditions with a mean air temperature of 10 ± 4 °C 81 ; further, although the exact water depths are unknown, the Jehol lakes had steep margins and sufficiently high depth-to-fetch ratios to develop stratification 46 , 82 .…”
Section: Discussionmentioning
confidence: 99%